Development of breeding lines with multiple stress tolerance to cold, drought, and high-temperature stress in rice (Oryza sativa L.) - Priyadarshi, Rahul; Yadav, Shailesh; Pettem, Mamatha; Venkateshwarlu, Challa; Pranesh, K. J.; Singh, Vikas K.; Kumar, Arvind (Springer, 2025)
Farmers and breeders recognize that multiple abiotic stresses occurring simultaneously are more harmful to crops than individual stress conditions. In this study, pedigree-based breeding was employed to develop multiple abiotic stress-tolerant rice breeding lines (MTU 1010/IRINMST-291), using stringent phenotypic selection for germination and seedling stage cold stress tolerance, reproductive stage drought stress, and reproductive stage high-temperature stress. Among the developed lines, IRINMST-007, IRINMST-338, IRINMST-418, and IRINMST-129 emerged as high-performing families under non-stress, drought, and high-temperature conditions during the reproductive stage. Additionally, IRINMST-007, IRINMST-418, and IRINMST-129 showed strong cold tolerance at the seedling stage and germination stage. These breeding lines have the potential to address food security challenges posed by abiotic stresses. A total of 110 parental polymorphic markers were used for single-marker analysis in the 180 selected F5 recombinant inbred lines. RM5344 were found associated with percent spikelet fertility at reproductive stage high-temperature stress with a phenotypic variance of 24%. RM5911 was found to be associated with grain yield at reproductive stage drought stress with a phenotypic variance of 11%. RM1019 was found associated with seedling growth under cold stress with a phenotypic variance of 18%. RM5344 was found associated with survival rate at seedling stage cold stress with a phenotypic variance of 19%. RM555 was found associated with vigor of germination at germination stage cold stress with a phenotypic variance of 18%. These markers can be used for molecular breeding programs to develop multi-stress tolerant rice varieties.